أثر تخفيض قيمة العملة على بعض المؤشرات الاقتصادية الكلية-دراسة تحليلية للاقتصاد للفترة )2019- ) 2000 - خلود بلهوشات; نسرين معمري (My University, 2021)
Currency devaluation is considered as one of the most common and important issues for the national bodies, which believes that its application as a reform policy is capable of achieving internal and external balance, and increasing the competitiveness of the economies of countries by activating exports and reducing imports, including improving and increasing the balance of payments balance, this may reflect on the internal balance of the state through an increase in the level of employment, economic growth and the stability of other economic indicators, and like other countries, Algeria adopted this policy at the beginning of the nineties due to the deficit of its balance of payments and the accumulation of its external debts. the purpose of the study was to determine the impact of the policy of devaluing the national currency on some external and internal macroeconomic indicators, in the context of unstable economic conditions. .................................................................. يعتبر تخفيض قيمة العملة من أكثر القضايا شيوعًا وأهمية بالنسبة لدول العالم الهيئات الوطنية، والتي ترى أن تطبيقها كسياسة إصلاحية قادر على تحقيقها التوازن الداخلي والخارجي، وزيادة القدرة التنافسية لاقتصادات الدول وذلك بتنشيط الصادرات وتقليص الواردات بما في ذلك تحسين وزيادة ميزان ميزان المدفوعات، وهو ما قد ينعكس على التوازن الداخلي للدولة من خلال زيادة مستوى التشغيل والنمو الاقتصادي واستقرار المؤشرات الاقتصادية الأخرى، وما شابه ذلك وفي بلدان أخرى، اعتمدت الجزائر هذه السياسة في بداية التسعينات بسبب العجز ميزان مدفوعاته وتراكم ديونه الخارجية. وكان الغرض من الدراسة لمعرفة مدى تأثير سياسة تخفيض قيمة العملة الوطنية على بعض العوامل الخارجية و مؤشرات الاقتصاد الكلي الداخلية، في سياق الظروف الاقتصادية غير المستقرة.